A Study of Health Education: Knowledge and Mothers' Attitudes Towards Pulmonary Tuberculosis Treatment Seeking Behavior in Bengkulu City - Susilawaty Susilawaty; Muhammad Kristiawan; Rambat Nur Sasongko (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The goal of this study was to determine the association between mothers' knowledge and behavior concerning pulmonary tuberculosis (TB) and their children's attitudes toward seeking treatment for pulmonary tuberculosis at health facilities in Bengkulu City. This is an observational study with a cross-sectional design. The research participants were women who had children who were at risk of TB, with 17 samples meeting the inclusion criteria but not the exclusion criteria. Inclusion criteria: Mothers with children are at risk of developing clinical tuberculosis as a result of household contact with smear-positive pulmonary tuberculosis patients. The child is under the age of five. Data collection techniques used include questionnaire testing, analysis of questionnaire, and measuring instruments as research instruments, collecting data with questionnaires, checking each respondent's answers in accordance with data collection procedures, and analyzing the data using computerized statistical methods. According to the findings, some respondents had limited awareness of TB illness in at-risk children, supported pulmonary TB disease in at-risk children, sought treatment for TB disease in at-risk children, and sought care for at-risk children at health facilities.